B2B Customer Loyalty in the Digital Transformation Era: Technology Experience and Financial Transparency - Firdaus Firdaus; Kusuma Ratnawati; Christin Susilowati (ARBITRASE: Journal of Economics and Accounting, 2026)
This systematic literature review (SLR) investigates the determinants of business-to-business (B2B) customer loyalty during the digital transformation era (2020-2025), focusing specifically on technology experience and financial transparency, two domains where empirical evidence remains fragmented. Following PRISMA 2020 guidelines, a comprehensive search across SciSpace, Google Scholar, and ArXiv yielded 749 initial records; after duplicate removal and systematic screening, 30 high-relevance empirical studies formed the primary evidence base. Technology experience enhances B2B loyalty through three mechanisms: AI-driven personalization, IoT-enabled real-time integration, and digital channel engagement. Financial transparency operates primarily through trust-building mechanisms, though direct empirical validation of pricing and cost transparency effects on B2B loyalty remains limited; blockchain shows conceptual promise but lacks rigorous empirical validation. The integration of technology experience and financial transparency creates synergistic loyalty effects exceeding individual contributions, moderated by industry sector, regional context, environmental turbulence, firm size, and relationship maturity. Trust emerges as the central mediator linking both dimensions to loyalty. The study advances B2B relationship marketing theory by integrating technology and transparency into a unified loyalty framework grounded in social exchange theory, service-dominant logic, transaction cost economics, and relational contract theory. Practically, B2B organizations should prioritize high-quality AI personalization systems, IoT-enabled service tracking, digital co-creation channels, and transparent financial practices while contextualizing strategies to moderating factors.